(untitled) (Journal of the Management Sciences, 2024)
The research evaluates human capital and sales growth of marketing firms in Igboland, Nigeria. The study was conducted to examine the relationship between work experience and sales growth as well as communication skill and sales growth. The researchers adopted the survey research design. The data used in the study were obtained from primary sources. A structured questionnaire was the major instrument for data collection. The study adopted the purposive sampling technique. Cronbach Alpha statistic was used to obtain the value of 0.85 as the instrument reliability ratio. Descriptive and inferential statistics were employed for data analysis. The findings reveal that there is a positive and significant relationship between work experience and sales growth; communication skill and sales growth. The study concludes that human capital boosts sales growth in marketing firms in Igboland Nigeria. The study recommends that marketing enterprises should always design programmes to boost the work experiences of their staff for enhanced sales growth. Also, the marketing enterprises should not relent in consistently improving the communication skills of their workers so that sales growth may always occure at a geometric progression.